A prospective study of postoperative outcome following splenectomy in immunocompromised thalassemia patient with special reference to CD4 count - Patole, Monali Madhukar; Patole, Mandar Madhukar; Ghosh, Manoranjan (International Journal of Contemporary Pediatrics, 2019)
Background: Thalassemia are inherited blood disorders that can result in the abnormal formation of hemoglobin. Splenectomy is indicated in the transfusion-dependent patient when hypersplenism increases blood transfusion requirement and prevents adequate control of body iron with chelation therapy. Ninety percent of recipients transfused with HIV antibody-positive blood are found to be HIV infected at follow-up. Prevailing literature on effects of splenectomy on CD4 count suggests that splenectomy causes an abrupt and prolonged increase in CD4 cell count. The aims and objectives this is an Institution based prospective observational study with the aim to observe postoperative outcome in immunocompromised thalassemic patients following splenectomy, postoperative outcome following splenectomy in a patient with low CD4 count and to analyze the effect of CD 4 count if any on different patients in terms of wound infection, chest infection , urinary tract infection or infection at any other site. Methods: The study included twenty immunocompromised thalassemia Patients attending in Pediatric Surgery OPD and admitted to Paediatric Surgery department of Medical college and hospital Kolkata with splenomegaly and HIV infection for splenectomy, between January 2015 to December 2016.Simple comparative analysis of gathered data was used to evaluate postoperative outcome m and the preop and the post op CD4 count levels of splenectomised thalassaemic patients. Results: Most patients in this study were in the (3-8) years age group and all are HIV positive patients with thalassemia. In this study author found there was increased CD4 count after splenectomy and postoperative period one patient developed postoperative oral candidiasis. Conclusions: HIV-infected thalassaemic patients on ART can now safely undergo major splenectomy surgery with encouraging results and in patients with a low CD4 count, there is no relation of CD4 count and splenectomy outcome.